Legal framework on affordable health: Comparative study between Malaysia and United States - Lee, Zi Yi (2023)
The title of the Final Year Project (FYP) is "Legal Framework on Affordable Health: Comparative Study between Malaysia and United States." The project aims to explore and compare the legal frameworks related to affordable health in Malaysia and the United States. The FYP will examine the different healthcare systems and policies in Malaysia and the United States, including the role of government in ensuring affordable health, the provision of health insurance, and the regulation of healthcare providers. It will also analyze the legal and regulatory frameworks that govern these healthcare systems, such as healthcare legislation, healthcare policies and budget in place. The FYP will utilize a variety of research methods, including literature review, and comparative legal analysis. The findings will contribute to the understanding of the legal frameworks for affordable healthcare in Malaysia and the United States and inform policy recommendations for improving access to healthcare services in both countries. Overall, the FYP aims to provide a comprehensive analysis of the legal frameworks related to affordable health in Malaysia and the United States, highlighting the laws and policies of each system and identifying opportunities for improvement.